Critique of Social Institutions in Gilles Deleuze’s and Felix Guattari’s Philosophy - Žukauskaitė, Audronė (Problemos, 2009)
The article discusses Deleuze’s and Guattari’s notions of society and state. In Anti-Oedipus, Deleuze and Guattari analyze the territorial, despotic and capitalist machines which are seen not as different stages of historical evolution but as different types of an abstract machine. In A Thousand Plateaus Deleuze and Guattari develop the mechanistic notion of the state: the state – form is an abstract machine or a diagram which can be actualized in different historical state forms. The state – form is juxtaposed to another type of assemblage called the nomadic war machine. If the state-form functions as a principle of unification and standardization, the war machine is seen as a principle of metamorphic transformations and innovations. Deleuze and Guattari’s theories of society and state are compared with Michel Foucault’s mechanistic notion of society. Deleuze contrasts his notion of control society to the notion of discipline society by Foucault. If the mechanisms of discipline are discontinuous and function in precise space areas, the mechanisms of control produce continuous and all-encompassing networks which totally merge with our corporeal existence.